Exploring the market to establish an advanced surgical community eye hospital. (January 2021) - Sood, Ishaana; Sabherwal, Shalinder; DasGupta, Shantanu; Chauhan, Naval; Chinnakaran, Anand; Nagappan, Sathish; Chandra, Suresh; Mishra, Madhur; Kumar, Mukesh; Mathur, Umang; Saksena, Ashish; Arora, Arun K
Developing countries often cite shortage of human resource, limited accessibility, low affordability, and asymmetric availability of health care resources as the provider end barriers to health care service utilization. Using the example of a market research project undertaken to establish an advanced surgical eye hospital in the Indian state of Uttar Pradesh, a decision-grid is constructed whereby health care providers' can make informed decisions regarding expansion and service delivery. The comparative and interpretive logic-based approach utilizes public domain data coupled with field research and is apt for those working in developing countries and/or resource-crunch settings. The paradigms laid out and discussed, provide building blocks for decision-making, which if harnessed effectively, have broad applicability in terms of reaching the previously unreached and ultimately in improving health outcomes.